High Intravascular Signal Arterial Transit Time Artifacts Have Negligible Effects on Cerebral Blood Flow and Cerebrovascular Reserve Capacity Measurement Using Single Postlabel Delay Arterial Spin-Labeling in Patients with Moyamoya Disease - Fahlström, M.; Lewén, A.; Enblad, P.; Larsson, E.-M.; Wikström, J. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Arterial spin-labeling-derived CBF values may be affected by arterial transit time artefacts. Thus, our aim was to assess to what extent arterial spin-labeling–derived CBF and cerebrovascular reserve capacity values in major vascular regions are overestimated due to the arterial transit time artifacts in patients with Moyamoya disease.MATERIALS AND METHODS: Eight patients with Moyamoya disease were included before or after revascularization surgery. CBF maps were acquired using a 3D pseudocontinuous arterial spin-labeling sequence, before and 5, 15, and 25 minutes after an IV acetazolamide injection and were registered to each patient’s 3D-T1-weighted images. Vascular regions were defined by spatial normalization to a Montreal Neurological Institute–based vascular regional template. The arterial transit time artifacts were defined as voxels with high signal intensity corresponding to the right tail of the histogram for a given vascular region, with the cutoff selected by visual inspection. Arterial transit time artifact maps were created and applied as masks to exclude arterial transit time artifacts on CBF maps, to create corrected CBF maps. The cerebrovascular reserve capacity was calculated as CBF after acetazolamide injection relative to CBF at baseline for corrected and uncorrected CBF values, respectively.RESULTS: A total of 16 examinations were analyzed. Arterial transit time artifacts were present mostly in the MCA, whereas the posterior cerebral artery was generally unaffected. The largest differences between corrected and uncorrected CBF and cerebrovascular reserve capacity values, reported as patient group average ratio and percentage point difference, respectively, were 0.978 (95% CI, 0.968–0.988) and 1.8 percentage points (95% CI, 0.3–3.2 percentage points). Both were found in the left MCA, 15 and 5 minutes post-acetazolamide injection, respectively.CONCLUSIONS: Arterial transit time artifacts have negligible overestimation effects on calculated vascular region-based CBF and cerebrovascular reserve capacity values derived from single-delay 3D pseudocontinuous arterial spin-labeling.ACAanterior cerebral arteryACZacetazolamideASLarterial spin-labelingATTarterial transit timeATToverlong arterial transit time where CBF is overestimatedATTundervery long arterial transit time where CBF is underestimatedCVRCcerebrovascular reserve capacityDiffabsolute differenceMMDMoyamoya diseasePCAposterior cerebral arterypCASLpseudocontinuous arterial spin-labelingPLDpostlabeling delaypppercentage points